SOCIAL PSYCHOLOGICAL FACTORS AFFECTING MENTAL DISORDERS OF NATIONAL GUARD MILITARY PERSONNEL (American Journal of Pedagogical and Educational Research, 2022)
In this article, opinions were expressed about the social psychological factors affecting the mental disorders of the National Guard military personnel.